Perancangan Aplikasi Sistem Informasi Geografis Tempat Wisata Di Bukittinggi Berbasis Web - Luthfi Hanif Al Hadi; Sularno (Journal Of Informatics And Busisnes, 2024)
Tourism is a sector that continues to develop and has an important role in the economic growth of a region. In this digital era, information technology plays a crucial role in supporting the development of the tourism sector. Geographic Information Systems (GIS) is a technology that is able to combine spatial and non-spatial data to provide information that is more comprehensive and easy to understand. In the midst of rapid technological developments, the use of web-based GIS has become an essential need to provide accessibility and convenience for users in obtaining information related to tourist attractions.